Biogas Production from Cow-Dung at Low Temperature by Integration of Microbial Electrolysis System - Khadka, Mamata; Bhatt, Puja; Sharma, Abinash; Pokhrel, Asmita; Katharia, Sanoj; Kandel, Pratap; Pandey, Lochan; Maharjan, Saru; Joshi, Jarina (Journal of Nepal Biotechnology Association, 2025)
Biogas, a sustainable energy source produced from anaerobic digestion of organic materials, holds significant potential in Nepal due to its abundant agricultural resources. This study investigates the production of biogas from cow dung integrating a microbial electrolysis cell (MEC) system to enhance performance of biogas production under low-temperature (15 ± 0.5°C). The biogas production process was assessed using a pilot-scale MEC system optimized at 2.5 V and 1:5 dilution. Performance metrics included biogas yield, methane content, and COD reduction. The MEC integration significantly improved biogas production, with a 20-fold increase at 2.5 V compared to the control reactor at 15°C. Scaling up to an 8.5 L pilot system demonstrated a fourfold increase in biogas production. Optimal conditions of 2.5 V and 1:5 dilution resulted in an 84.21% COD reduction at 15°C, increasing to 88.28% at the pilot scale. Molecular identification of microbial consortia isolated from biogas production medium were specifically Bacillus cereus, Bacillus paramycoides, Bacillus licheniformis and Priestia flexa which play crucial role in organic matter degradation and electron transfer in MEC operation at low temperature. Hence, integration of MEC technology substantially enhances biogas production and organic waste treatment efficiency, particularly at low temperature.